Pseudomonas taiwanensis biofilms for continuous conversion of cyclohexanone in drip flow and rotating bed reactors - Heuschkel, Ingeborg (Eng Life Sci, 2021)
In this study, the biocatalytic performance of a Baeyer‐Villiger monooxygenase (BVMO) catalyzing the reaction of cyclohexanone to ε‐caprolactone was investigated in Pseudomonas biofilms. Biofilm growth and development of two Pseudomonas taiwanensis VLB120 variants, Ps_BVMO and Ps_BVMO_DGC, were evaluated in drip flow reactors (DFRs) and rotating bed reactors (RBRs). Engineering a hyperactive diguanylate cyclase (DGC) from Caulobacter crescentus into Ps_BVMO resulted in faster biofilm growth compared to the control Ps_BVMO strain in the DFRs. The maximum product formation rates of 92 and 87 g m(–2) d(–1) were observed for mature Ps_BVMO and Ps_ BVMO_DGC biofilms, respectively. The application of the engineered variants in the RBR was challenged by low biofilm surface coverage (50–60%) of rotating bed cassettes, side‐products formation, oxygen limitation, and a severe drop in production rates with time. By implementing an active oxygen supply mode and a twin capillary spray feed, the biofilm surface coverage was maximized to 70–80%. BVMO activity was severely inhibited by cyclohexanol formation, resulting in a decrease in product formation rates. By controlling the cyclohexanone feed concentration at 4 mM, a stable product formation rate of 14 g m(–2) d(–1) and a substrate conversion of 60% was achieved in the RBR.